2018
DOI: 10.1103/physrevc.97.014909
|View full text |Cite
|
Sign up to set email alerts
|

ψ(2S) versus J/ψ suppression in proton-nucleus collisions from factorization violating soft color exchanges

Abstract: We argue that the large suppression of the ψ(2S) inclusive cross-section relative to the J/ψ inclusive cross-section in proton-nucleus (p+A) collisions can be attributed to factorization breaking effects in the formation of quarkonium. These factorization breaking effects arise from soft color exchanges between charm-anticharm pairs undergoing hadronization and comoving partons that are long-lived on time scales of quarkonium formation. We compute the short distance pair production of heavy quarks in the Color… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 61 publications
1
42
0
Order By: Relevance
“…Further, the increasing experimental precision of collider data opens up the possibility of computing the polarizations of the higher charmonium states in the CGC+NRQCD framework . In particular, the good description of data obtained for ψ(2s) yields [38,48] suggests that this framework may also describe the polarization of this meson. Measurements of the χ cJ states [82] give access to the 3 P [1] J channel [83].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the increasing experimental precision of collider data opens up the possibility of computing the polarizations of the higher charmonium states in the CGC+NRQCD framework . In particular, the good description of data obtained for ψ(2s) yields [38,48] suggests that this framework may also describe the polarization of this meson. Measurements of the χ cJ states [82] give access to the 3 P [1] J channel [83].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, by taking into account both the saturation effect and the comover effect simultaneously, the nuclear suppressions of J/ψ and ψ(2S) can be described well in the small-x formalism. The details of a calculation of ψ(2S) production in the small-x formalism will be reported separately [76].…”
Section: Discussionmentioning
confidence: 99%
“…All input parameters in the initial dipole amplitude at x 0 = 0.01 are determined by DIS global fits to HERA data. In our numerical computations, we take the initial saturation scale Q 2 sp,0 = 0.168 GeV 2 for the proton and Q 2 sA,0 = 2 Q 2 sp,0 for nuclei as discussed in [2,3]. High values of N ch are achieved by allowing the initial saturation scales of both the projectile and target to fluctuate to large values, corresponding to a fluctuation of large x parton configurations in these rare events.…”
Section: Cgc Frameworkmentioning
confidence: 99%
“…Heavy flavor (D) and quarkonium (J/ψ) production in minimum bias proton-proton(p + p) and protonnucleus (p + A) collisions at RHIC and LHC have been studied extensively in the Color-Glass-Condensate (CGC) effective field theory over the last several years [1,2,3,4,5,6,7]. These works demonstrated that quantitative descriptions of the transverse momentum and rapidity distributions could be achieved in these collisions.…”
Section: Introductionmentioning
confidence: 99%